Identifikasi Spesies Dan Indeks Keragaman Lalat Pada Fasilitas Penampungan Sampah Rumah Sakit Umum Di Yogyakarta - Mulyaningsih, Budiyanti (Politeknik Kementerian Kesehatan Banjarmasin, 2023)
Several fly species have been related to health issues as mechanical and biological vectors of specific diseases. The purpose of this research was to identify the species of nonbiting fly and the diversity index of flies in the waste shelter at several public hospitals in Yogyakarta. This study used a descriptive observational method with a cross-sectional design. Flies were collected using an insect net at several waste shelters at several public hospitals in Yogyakarta. Identification of flies was carried out directly based on the morphological characteristics of flies. The diversity of fly species was analyzed by Shannon Winner's diversity index. Based on the capture, 3 species of flies were identified in the medical waste shelter and 6 species of flies were identified in the non-medical waste shelter. The number of captured flies in the medical waste shelter was 6, while in the non-medical waste shelter it was 211. The diversity index in the medical waste shelter was 1.011, while in the non-medical waste shelter it was 0.787. The conclusion of this study identified 6 species of flies, known as Musca domestica, Sarcophaga sp., Chrysomyia megachephala, Lucillia sp., Calliphora sp., and Muscina sp. Fly diversity in medical waste shelters was in the low category, while fly diversity in non-medical waste shelters was in the medium category.